The Risks of Bail in Brazil: The Figure of the Guarantor from the Perspective of the Brazilian Supreme Court in Cases Involving Family Property (Global Journal of Human-Social Science, 2024)
The purpose of this article is to examine the legal and jurisprudential treatment of guarantors of rental contracts of a residential and commercial nature The examination of the legal effects arising from the decision to act as guarantor is also sought To this end it is mentioned that there is within the framework of normative infrakonstitutional express command of safeguarding the family good institute whose bias is the preservation of the fundamental right to housing human and social right positivized in article 6 of the Constitution of the Federal Republic of Brazil This legal backing derives from the intrinsic relationship between adequate housing and the right to life and the dignity of the human person On the other hand it has to be said that the legislation itself which makes the debtor s property unbinding excludes the guarantor And since the bail is a personal guarantee as a rule provided free of charge there is a profound divergence of understanding among the members of the highest court in Brazil about the constitutionality of the seizure of family property of the tenant of the lease contract For this reason it turns out to be relevant the study of four important judges Extraordinary Recourses 407 688 612 360 605 709 and 1 307 334 that demonstrate over the years the position of the Supreme Court on the subject
Keywords: guarantor's family property; impenetrability of a single residential property; bail on rent; risk of bail and right to housing